Global energy trade flows and constraints on conventional and renewable energies: A computable modeling approach - Ole Grogro (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2012)
This paper introduces the computable partial equilibrium energy model 'Global Resource Extraction and Energy Transformation' (GREET), its structure, assumptions and the outcomes of two exemplary scenarios. GREET is characterized by a comprehensive modelling of constraints on the diffusion of renewable energy, where physical constraints on the regional deployment of renewable energy technologies are complemented by the need to provide storage capacities for renewable production of electricity. The consumption of conventional primary energy carriers, on the other hand, is constrained by regional resource endowments as well as the need for capacity investments in primary energy carrier extraction-, trade- and ransformation processes. In comparison to most contrastable global energy models, there is an explicit modelling of interregional trade flows in primary energy carriers, for which originating and destinating regions of the energy trades can clearly be specified. Thus, GREET, covering global primary energy trades for eleven world model regions, is very applicable for looking into future developments of energy trade flows. At the same time GREET doesn't miss to cover the point that predominantly renewable based energy systems of the future are confined by constraints on renewable energy production technologies, such as the need to provide electricity storage capacities.
Keywords: 330; Energiekonsum; Außenwirtschaft; Partielles Gleichgewicht; Bottleneck; Fossiler Energieträger; Regenerative Energie; Theorie; Welt